Investigating The Role of Sustainable Practices in Construction Materials Handling: A Pathway Towards SDG Integration - Murali, Kumar; Nagapan, Sasitharan (Journal of Structural Monitoring and Built Environment, 2025)
This research explores the integration of sustainable practices in construction materials handling to enhance sustainability and support the achievement of Sustainable Development Goals (SDGs). The study aims to identify current barriers in construction materials handling practices to pinpoint inefficiencies and areas ripe for improvement in sustainability, determine the potential benefits of implementing sustainable practices in construction materials handling on the achievement of Sustainable Development Goals (SDGs) and propose strategies for integrating sustainable practices into construction materials handling processes effectively.. Using quantitative data collection and analysis, the study reveals that sustainable materials handling practices lead to cost savings (mean = 4.06) and that insufficient regulatory support is a major barrier (mean = 4.0). Enhanced reputation (mean = 4.15) and prioritizing green building certifications (mean = 4.19) are highlighted as key benefits and strategies, respectively. Reliability analysis shows Cronbach's Alpha values between 0.835 to 0.916, indicating good to excellent reliability, with an overall value of 0.888. These findings emphasize the need to address regulatory barriers and focus on green certifications to foster sustainable practices in construction materials handling, aligning the industry with SDGs.